Bowen’s disease mimicking lichen simplex chronicus in a 56-year-old Filipino man: A case report - Karim, Cynthia Angela; Ryan, Elisabeth; Ugalde, Reynaldo (UI Scholars Hub, 2024)
Background: Bowen's disease (BD) is a chronic skin condition presenting clinically as erythematous plaques with scales on sun-exposed areas. BD is generally regarded as a squamous cell carcinoma (SCC) in situ. In contrast, lichen simplex chronicus (LSC), also known as neurodermatitis, is a chronic skin disorder characterized by extreme pruritus. In LSC, lichenified plaques form primarily on accessible body parts due to repeated scratching or rubbing. Case Illustration: A 56-year-old male presented with a solitary chronic plaque with a central ulcer and erosions on his left upper thigh. Dermoscopy findings were glomerular vessels and a scaly surface, which are typical features of BD. A skin punch biopsy showed numerous atypical keratinocytes with mitotic figures in the epidermis, which is also typical of BD. The patient underwent carbon dioxide (CO2) laser treatment in our institution. Discussion: The natural course of LSC and BD is usually prolonged, and their similarities in clinical presentation require appropriate examination. Dermoscopy findings and histopathology results may help determine the precise diagnosis and appropriate treatment. Conclusion: BD lesions can mimic LSC; therefore, histopathology examination is the gold-standard to establish the diagnosis of BD. Careful and precise examination should be done to distinguish the similarities between LSC and BD.